2021
DOI: 10.3389/fpls.2021.682439
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Linkage β-1,3/1,4-Glucan Oligosaccharides Induce Defense Responses in Hordeum vulgare and Arabidopsis thaliana

Abstract: Plants detect conserved microbe-associated molecular patterns (MAMPs) and modified “self” molecules produced during pathogen infection [danger associated molecular patterns (DAMPs)] with plasma membrane-resident pattern recognition receptors (PRRs). PRR-mediated MAMP and/or DAMP perception activates signal transduction cascades, transcriptional reprogramming and plant immune responses collectively referred to as pattern-triggered immunity (PTI). Potential sources for MAMPs and DAMPs are microbial and plant cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…Oligosaccharides with mixed linkages, β-1,3/1,4-glucan (β-1,3/1,4-MLG), are plentifully found in bacteria, oomycetes, symbionts, pathogenic or non-pathogenic fungi, and monocot plants. Barghahn et al examined mutants of Arabidopsis innate-immunity signaling as well as more than 100 Arabidopsis ecotypes and hypothesized that β-1,3/1,4-MLG oligosaccharides contain the two-fold capability to perform as immune active microbe-associated molecular patterns (MAMPs) and danger-associated molecular patterns (DAMPs) in both monocot and dicot plants [ 107 ]. Additionally, Rebaque et al suggested that MLGs work as a cluster of carbohydrate-established molecular patterns and are noticed by plants to initiation their immune reactions and disease endurance [ 108 , 109 ].…”
Section: Glcnac Metabolic Engineering For Reducing the Virulence Of P...mentioning
confidence: 99%
“…Oligosaccharides with mixed linkages, β-1,3/1,4-glucan (β-1,3/1,4-MLG), are plentifully found in bacteria, oomycetes, symbionts, pathogenic or non-pathogenic fungi, and monocot plants. Barghahn et al examined mutants of Arabidopsis innate-immunity signaling as well as more than 100 Arabidopsis ecotypes and hypothesized that β-1,3/1,4-MLG oligosaccharides contain the two-fold capability to perform as immune active microbe-associated molecular patterns (MAMPs) and danger-associated molecular patterns (DAMPs) in both monocot and dicot plants [ 107 ]. Additionally, Rebaque et al suggested that MLGs work as a cluster of carbohydrate-established molecular patterns and are noticed by plants to initiation their immune reactions and disease endurance [ 108 , 109 ].…”
Section: Glcnac Metabolic Engineering For Reducing the Virulence Of P...mentioning
confidence: 99%
“…The importance of cell walls for plant defense is demonstrated by the abundance of cell wall degrading enzymes that microbial pathogens secrete in order to successfully invade plant tissues ( Glass et al, 2013 ; Quoc and Bao Chau, 2017 ; Hao et al, 2019 ). The plant immune system in turn reacts to cell wall degradation products such as oligogalacturonides (OGs; Ferrari, 2013 ; Davidsson et al, 2017 ), hemicellulose derived β-1,3-1,4-glucan oligosaccharides ( Barghahn et al, 2021 ; Yang et al, 2021 ), arabinoxylan oligosaccharides ( Mélida et al, 2020 ), and cellulose derived oligosaccharides ( Zarattini et al, 2021) . Plant cell walls consist of a complex meshwork of polysaccharides, where cellulose microfibrils are cross-linked by various hemicelluloses and embedded in a pectic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The specific and direct recognition of a DAMP/MAMP by the ECD of its PRR counterpart receptor trigger the formation of a ligand-PRRs complex, that involves additional PRRs that directly (co-receptors) or indirectly contribute to the functionality of the recognition complex through the stabilization of ligand-receptor binding or activation of KD of some PRRs from the complex, which in turn initiates phosphorylation events and PTI-associated responses (1)(2)(3). Several new glycoligands (DAMPs/MAMPs) derived from cell walls or extracellular matrixes from plants or microorganisms that trigger immune responses in plants have been recently described ((9-20), (31)(32)(33)(34)). These new carbohydrate-based elicitors include oligosaccharides derived from plant cell wall β-glucans, like MLGs (e.g., MLG43, MLG34 and MLG443) or cellulose (e.g., CEL2, CEL3, CEL4, CEL5, CEL6), or from arabinoxylans and mannans polysaccharides (16,18,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Several new glycoligands (DAMPs/MAMPs) derived from cell walls or extracellular matrixes from plants or microorganisms that trigger immune responses in plants have been recently described ((9-20), (31)(32)(33)(34)). These new carbohydrate-based elicitors include oligosaccharides derived from plant cell wall β-glucans, like MLGs (e.g., MLG43, MLG34 and MLG443) or cellulose (e.g., CEL2, CEL3, CEL4, CEL5, CEL6), or from arabinoxylans and mannans polysaccharides (16,18,(31)(32)(33). These glycoligands have been added to the list of previously characterised oligosaccharides, which include oligoglycans from fungal chitin (e.g., CHI6) or plant pectins (e.g., OGs), which are perceived by LysM-PRRs and WAK1/2/FER1-PRRs, respectively (40,47,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation